Elementary school teachers' implementation of differentiated curriculum in mixed ability classes - Ulaş, Mine (Eastern Mediterranean University (EMU), 2011)
The purpose of this study is to investigate the elementary school teachers’ implementation of differentiated curriculum in mixed ability classes in Nicosia in the Turkish Republic of Northern Cyprus (TRNC). Quantitative data were collected from nineteen public and three private elementary schools to investigate the extent that differentiated curriculum is used in elementary grades. A total of 395 teachers participated in the study. For the pilot study 96 teachers participated and for the actual study data were collected from 299 teachers. The scale for measuring differentiated curriculum prepared by Susan Hallam and Judith Ireson`s (2005) was translated into the teachers` native language, Turkish. The instrument prepared by the researcher comprises two sections with a total of 32 items; the first section consists of four items to elicit demographic features of the teachers (gender, school type, years of experience and grade level) and the second section is a Scale for Measuring Implementation of Differentiated Curriculum (SMIDC) which measures the participants’ implementation of differentiated curriculum in mixed ability classes, and it consists of twenty eight statements which can be responded on a five-point Likert type scale. The data obtained from the SMIDC scale were analyzed by using the Statistics Package for Social Sciences (SPSS) program. Analysis of the data included the elementary school teachers’ implementation of differentiated curriculum and how this implementation differed in terms of teachers` gender, school location, grade level, years of experience, and type of school (private or public). The findings revealed that elementary school teachers in the Nicosia district have positive views on the implementation of differentiated curriculum in mixed ability classes. Most of the teachers are aware of differentiated curriculum and they are implementing it in mixed ability classes. With regard to the differences between the implementation of differentiated curriculum and teachers` gender, school location, type of school, grade level, and years of experience, the findings show that there is a significant difference between the teachers` implementation of differentiated curriculum and the grade level they teach. However, it was found that there is no significant difference between the teachers’ implementation of differentiated curriculum and teachers` gender, school location, school type, and years of experience.
Master of Education in Educational Sciences. Thesis (M.Ed.)--Eastern Mediterranean University, Faculty of Education, Dept. of Educational Sciences, 2011. Supervisor: Assist. Prof. Dr. Hüseyin Yaratan.
Keywords: Educational Sciences; Teachers - Elementary Schools - Cyprus, North